PENERAPAN VIDEO ANIMASI DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM GUNA MEMPERDALAM PEMAHAMAN PESERTA DIDIK DI ERA DIGITAL - Nasrodin, Nasrodin; Muttaqin, Ahmad Izza; Dhani, Dhavid Ahmad (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This study aims to explain the use of animated video learning media in the subject of Islamic Cultural History in increasing the understanding of grade VIII A students at MTs Negeri 7 Banyuwangi. The research method used is qualitative descriptive with the subject of research consisting of teachers of Islamic Cultural History subjects and grade VIIIA students. Data collection techniques include observation, interviews, and documentation. Data analysis techniques used by Miles and Huberman's interactive model consisting of data collection, data reduction, data presentation and Conclusion Drawing and Verification. The results showed that the application of learning media in the form of animated videos involved the stages of planning, implementation, and evaluation. The planning stage involves preparing material, preparing lesson plans, and motivation for students. The implementation stage includes the use of learning media by preparing material and facilitating interaction with students. The evaluation stage is carried out through giving questions or exercises to students. The results also showed an increase in students' understanding of the material taught. It is hoped that the results of this research can provide concrete and relevant recommendations for curriculum development and innovative and effective teaching strategies in learning Islamic Cultural History.